Management efficiency and school culture, and teacher performance in Indonesian vocational school during fiscal austerity - Agus Purnomo; Sudarwan Danim; Azizatul Khairi (Jurnal Konseling dan Pendidikan, 2026)
This research is motivated by the 2025 national budget efficiency policy which impacts limited education funding in the regions, especially when committee fees cannot be collected, so schools need to optimize management efficiency and build a strong school culture to maintain teacher performance. This study aims to analyze the influence of management efficiency and school culture on the performance of public vocational high school teachers in North Bengkulu Regency. The approach used is quantitative with a survey method of 57 teachers selected using the Isaac and Michael formula. Data were analyzed through descriptive statistics, validity and reliability tests, linear regression, and multiple determination coefficients using SPSS 22. The results show that management efficiency and school culture have a positive and significant effect on teacher performance with a simultaneous contribution of 63.6%, where management efficiency is more dominant. The uniqueness of this study lies in the simultaneous testing of both variables in the context of the national budget efficiency policy, thus providing a contextual empirical picture. This research has implications for the importance of formulating integrated and sustainable school management policies and contributes to providing empirical evidence regarding effective strategies for maintaining teacher performance amidst limited education budgets.